Aplikasi Pengenalan Ucapan Sebagai Pengatur Mobil Dengan Pengendali Jarak Jauh - Ajulian Z., Ajub; Hidayatno, Achmad; Widyanto Tri Saksono, Muhammad (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
Growth in Digital signal processing technology gives positives influences in human life. One of the branch of science that gives significant influence is digital speech processing. It can be expand into some applications that make human life easier. Digital speech processing is appropriate to speech recognition.Speech recognition is used to arrange the movement of remote control car. The remote control car will move according to our speech.Â This final project is closely related with speech recognition.Â The LPC (Linear Predictive Coding) method will extract the speech signal features and HMM (Hidden Markov Model) to modelling the speech signal are used. It is done by comparing model from extractingÂ feature that is available in HMM modelling. Models will be used in the speech recognition process, if the models have highest level of conformity.The experiment has been done in two conditions, i.e ideal condition in room wih low noise level and unideal condition in room with noise. Result of the experiment from the whole sistem performace at ideal condition is 97,71% for people that have been inputed in the database, and 95,42% for people which have not been inputed in the database. Result of the experiment of database say it regulary is 97,14%. Result of the experiment of database at unideal condition is 54,28% for inputing word at noisy area, result of the experiment of database for inputing word at high frequency from siren voice is 98,57% and result of the experiment of inputing similar word with database is 97,6%Keywords: speech recognition, LPC, HMM